"Enough Wandering Around!": Life Trajectories, Mobility, and Place Making in Neoliberal Academia. Issue 2 (3rd April 2019) - Manzi, Maya; Ojeda, Diana; Hawkins, Roberta
Abstract : This article analyzes the life trajectories of twelve early-career geographers in relation to their life–work experiences in an increasingly neoliberal academia and its constant demands of hypermobility. Using (auto)ethnographic research methods, it delves into the manifestations and effects of the pervasive myth of the detached, always ready-to-move scholar. We analyze the role of mobility in imaginaries and practices of academia and its close relationship with privilege and precarity. Our findings show how academic work is inescapably located despite the systematic erasure of the bodies, places, and networks that scholars are part of. By taking into account the centrality of place making in academic experience, our conclusions point to more comprehensive ways in which academic mobility can be understood, reflected on as part of geographers' professional training, and transformed.